Christian Federation of Malaysia (CFM) and National Evangelical Christian Fellowship (NECF): their responses to contemporary issues - Mhd Omar, Mohd Faridh Hafez; Ibrahim, Haslina (IIUM Press, 2017)
Malaysia is a multi-ethnic, multi-racial and multi-religious state. The Muslims constitute 61.3%, Christians 9.1%, Hindus 6.3%, Buddhist 19.2%, Sikhs 0.9% and others 2.6% of the population of Malaysia. This study examines the stated position and views of the Christian Federation of Malaysia (CFM) and the National Evangelical Christian Fellowship (NECF) of Malaysia on religious freedom, the Islamization approach in Malaysia and the use of the word ‘Allah’ by Christians. This study argues that examination of the stated views and responses of non-Muslim citizens of Malaysia about issues of freedom of religion, Islamization approach and the use of the word ‘Allah’ by Malaysia’s non-Muslim citizens is important for the preservation and maintenance of religious and racial harmony and political stability in the country. The study used qualitative method of data collection. The study examined CFM and NECF online data official documents and newspapers and conducted in-depth interviews as main sources of data collection. The study found that the objectives of the CFM and NECF and the issues that led to their establishment and their focus/target group are different. Yet, both organizations are similarly concerned with the objectivity of their organization and want to honor the spirit of the Federal Constitution in their stated positions and responses toward issues that are related to Christian interests and rights to freedom of religion and the use of the word ‘Allah’. The study found that CFM and NECF have suggested interpretations of the Federal Constitution in such a manner that can preserve religious harmony, freedom of religion and respect for the rights of followers of other religions in Malaysia. The study also found that the CFM and NECF also suggest that one way to overcome religious differences and potential inter-religious conflict is to promote inter-religious dialogues among the followers of different religions in Malaysia. Finally, the study, among others, recommends that government agencies and religious institutions play a more pro-active role in making policies on propagating and engaging adherents of various religions in Malaysia.